Knowledge model based on destination management system framework for Chinese gay tourist in Bangkok by using knowledge engineering - Zaiqi Gao (2019)
© 2019 IEEE. This study is to describe how the knowledge model based on the Destination Management System framework by using Knowledge Engineering can develop the Chinese gay tourist's travelling efficiency when they carry the gay-leisure aspect at the Bangkok. Knowledge engineering methodology provides the process to identify the problem and elicit the knowledge from the experts' experience, research articles, and documents. The knowledge model based on the Destination Management System(DMS) framework matches the needs and requirements of the knowledge worker. The ontology identification and development to organize, distribute and utilize the knowledge were followed by the knowledge worker and expert needs which under the framework of the DMS.